Case of Ankylosing Spondylitis - Shukla, Chetna (Homœopathic Links, 2015)
All the beauty of homeopathy and the human mind got revealed to me when this patient's X-rays with stage II ankylosing spondylitis turned back to normal. The impetus from Rhus toxicodendron gave him an opportunity to lead a healthy life. His HLA B27 was positive. The disease returned in the knee as effusion. Eventually he did not choose homeopathy to work together with me to “mind his min.” This article is the understanding of how I understand this drama and integrate the lessons in my practice.
Keywords: Autoimmune disease; Ankylosing spondylitis; Curability quotient; Belief of disease; Rhus toxicodendron; Overstretching; Return of disease; Aphorism §33